Depression and Mania in Bipolar Disorder - Tondo, Leonardo; H. Vazquez, Gustavo; J. Baldessarini, Ross (Current Neuropharmacology, 2017)
Background: Episode duration, recurrence rates, and time spent in manic and depressive phases of bipolar disorder (BD) is not well defined for subtypes of the disorder. Methods: We reviewed the course, timing, and duration of episodes of mania and depression among 1130 clinically treated DSM-IV-TR BD patients of various types, and compared duration and rates as well as total proportion of time in depressive versus manic episodes during 16.7 average years at risk. Results: As expected, episodes of depressions were much longer than manias, but episode-duration did not differ among BD diagnostic types: I, II, with mainly mixed-episodes (BD-Mx), or with psychotic features (BD-P). Recurrence rates (episodes/year) and proportion of time in depression and their ratios to mania were highest in BD-II and BD-Mx subjects, with more manias/year in psychotic and BD-I subjects. In most BD-subtypes, except with psychotic features, there was more time in depressive than manic morbidity, owing mainly to longer depressive than manic episodes. The proportion of time in depression was highest among those who followed a predominant DMI course, whereas total time in mania was greatest in BD with psychotic features and BD-I. and with an MDI course. Conclusions: Subtypes of BD patients differed little in episode-duration, which was consistently much longer for depression. The findings underscore the limited control of bipolar depression with available treatments.
Keywords: depression